SECONDARY SCHOOL STUDENTS’ DEVELOPING STRATEGIES FOR BUILDING RESILIENCE AND MOTIVATION FOR PHYSICAL READINESS AND MILITARY PREPAREDNESS (Physical Culture and Sport: Scientific Perspective, 2024)
The article explores the development of resilience and motivation in secondary school students for physical readiness and military preparedness, navigating challenges and pursuing passions, with a focus on key aspects drawn from the experiences of leading countries worldwide. A comparative analysis highlights the differences between Ukraine and its partner countries in preparing young people for national defence. Two notable features are central to Ukraine’s context: first, the country is currently enduring Russia’s armed aggression, and second, the status of internally displaced persons (IDPs) as estimated tens of thousands of Ukrainians, including schoolchildren. The article also addresses the significant legislative changes in Ukraine that have strengthened the military and patriotic components of education across all institutions.The study emphasizes the need for fostering motivation among students to defend Ukraine. Key conditions include raising awareness among all participants in the educational environment about the importance of the issue, addressing the pedagogical gap between the demanding expectations of teachers of the “Defence of Ukraine” subject and the actual abilities of students to meet these expectations, and ensuring that schools have the necessary educational and technical facilities to support the “Defence of Ukraine” curriculum.Noteworthy, the article explores the psychological aspect of preparing students for military readiness, emphasizing the importance of building mental resilience alongside physical strength. In a time of national crisis, such as the ongoing war in Ukraine, students must develop not only physical capabilities but also the mental toughness required to face adversity. This includes fostering a sense of responsibility, patriotism, and the will to defend their country. The author highlights the role of educators and schools in creating environments that nurture these psychological traits, ensuring that students are emotionally prepared for potential challenges. Additionally, the curriculum must incorporate strategies that encourage a positive mindset and the ability to remain motivated, even under difficult circumstances, which is essential for long-term engagement in national defence efforts.To recapitulate, the author stresses the critical role of physical education, highlighting the importance of students attaining sufficient physical fitness as an essential component of their preparation for military service.
Keywords: motivational conditions; military preparedness; military-patriotic education; physical education; Ukraine; NATO